Contagious cooperation, temptation, and ecosystem collapse - Andries Richter; Daan van Soest; Johan Grasman (Fondazione Eni Enrico Mattei (FEEM), 2013)
Real world observations suggest that social norms of cooperation can be effective in overcoming social dilemmas such as the joint management of a common pool resource - but also that they can be subject to slow erosion and sudden collapse. We show that these patterns of erosion and collapse emerge endogenously in a model of a closed community harvesting a renewable natural resource in which individual agents face the temptation to overexploit the resource, while a cooperative harvesting norm spreads through the community via interpersonal relations. We analyze under what circumstances small changes in key parameters (including the size of the community, and the rate of technological progress) trigger catastrophic transitions from relatively high levels of cooperation to widespread norm violation - causing the social-ecological system to collapse.
Keywords: C73; D62; D64; Q20; 330; Social Norms; Common Pool Resource; Co-Evolution; Resilience; Alternative Stable States